HAKIKAT REWARD DALAM PERSPEKTIF NILAI-NILAI PENDIDIKAN ISLAM - Maulida, Sri Aqilah; Sihotang, Abdi Ardiansyah; Kahairani, Lusi (TARBAWI:Journal on Islamic Education, 2023)
This research discusses the concept of rewards in Islamic education, focusing on the objectives, principles, and forms of rewards that can be given to students. The literature study method with a qualitative approach is used to analyze the information contained in scientific literature relevant to the research topic. The results revealed that rewards in Islamic education are recognition and appreciation given to learners as a result of their efforts, achievements, or positive behavior. Rewards have functions as motivation, reinforcement, and recognition. In giving rewards, the principles that must be considered include assessment based on behavior, restrictions in giving rewards, deliberation in determining rewards, and focus on process rather than results. This research is expected to provide insights and practical guidance for educators, parents, and related parties in strengthening Islamic education that is oriented towards good values.